Hotspots of dendritic spine turnover facilitate clustered spine addition and learning and memory - Adam C. Frank (Nature Portfolio, 2018)
Structural remodeling of dendritic spines is thought to be a mechanism of memory storage. Here, the authors look at how spine turnover and clustering predict future learning and memory performance, and see that a genetically modified mouse with enhanced spine turnover has enhanced learning.